Stopping over-medication of people with an intellectual disability, autism or both (STOMP) in England part 2 – the story so far. Issue 1 (19th September 2018) - Branford, David; Gerrard, David; Saleem, Nigget; Shaw, Carl; Webster, Anne
Abstract : Purpose: The STOMP programme – stopping the over-medication of people with an intellectual disability, autism or both is a three-year programme supported by NHS England. Concern about the overuse of antipsychotic drugs has been a constant theme since the 1970s. However, despite a multitude of guidelines the practice continues. The report into the events at Winterbourne View not only raised concerns about the overuse of antipsychotic drugs but of antidepressants. Part 1 presented the historical background to the use of psychotropic drugs for people with an intellectual disability, autism or both. The purpose of this paper (Part 2) is to present the approach adopted to reduce over-medication (the "Call to Action") and the progress so far at the half way stage. Design/methodology/approach: The "Call to Action" methodology is described in a Manchester University report – mobilising and organising for large-scale change in healthcare "The Right Prescription: A Call to Action on the use of antipsychotic drugs for people with dementia". Their research suggested that a social mobilising and organising approach to change operates could provide a mechanism for bringing about change where other approaches had failed. Findings: The adoption of the "Call to Action" methodology has resulted in widespread acknowledgement across intellectual disability practice that overuse of psychotropic medication and poor review was resulting in over-medication. Many individual local programmes are underway (some are described in this paper) however to what extent the overall use of psychotropic drugs has changed is yet to be evaluated. Originality/value: STOMP is part of an English national agenda – transforming care. The government and leading organisations across the health and care system are committed to transforming care for people with intellectual disabilities autism or both who have a mental illness or whose behaviour challenges services. This paper describes a new approach to stopping the over-medication of people with an intellectual disability, autism or both.